A Conserved Di-Lysine Motif in the E2 Transactivation Domain Regulates MmuPV1 Replication and Disease Progression - Jessica Gonzalez; Marsha DeSmet; Elliot J. Androphy (Pathogens)
The papillomavirus E2 protein regulates the transcription, replication, and segregation of viral episomes within the host cell. A multitude of post-translational modifications have been identified which control E2 functions. A highly conserved di-lysine motif within the transactivation domain (TAD) has been shown to regulate the normal functions of the E2 proteins of BPV-1, SfPV1, HPV-16, and HPV-31. This motif is similarly conserved in the E2 of the murine papillomavirus, MmuPV1. Using site-directed mutagenesis, we show that the first lysine (K) residue within the motif, K112, is absolutely required for E2-mediated transcription and transient replication in vitro. Furthermore, mutation of the second lysine residue, K113, to the potential acetyl-lysine mimic glutamine (Q) abrogated E2 transcription and decreased transient replication in vitro, while the acetylation defective arginine (R) mutant remained functional. Both K113 mutants were able to induce wart formation in vivo, though disease progression appeared to be delayed in the K113Q group. These findings suggest that acetylation of K113 may act as a mechanism for repressing MmuPV1 E2 activity.